2017
DOI: 10.3390/en10081234
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Effects of Moisture Content and Inherent Clay Minerals on the Cohesive Strength of Remodelled Coal

Abstract: Injecting water into a coal seam to enhance the cohesive strength of coal and thus minimize and reduce the coal wall spalling risk must be considered in underground coal mining systems. In general, coal with low cohesive strength contains clay minerals which may affect the stability of coal by interacting with water. Therefore, the coupled effects of moisture content and inherent clay minerals on the physical properties (i.e., cohesive strength and internal friction angle) of coal samples should be addressed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(35 reference statements)
3
2
3
1
Order By: Relevance
“…However, the cohesion of coal being reduced after the threshold moisture content was explained by the reduction of friction between adjacent coal particles. In addition to the similar trend, the ranges of cohesive strength and moisture content in this study are very close to those in the study conducted by Zhang et al (2017) [20], interestingly. Meanwhile, the effect of moisture content on the friction angle of the coal specimen was also studied (Figure 7b).…”
Section: Effect Of Moisture Content On the Strength Properties Of Coalsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the cohesion of coal being reduced after the threshold moisture content was explained by the reduction of friction between adjacent coal particles. In addition to the similar trend, the ranges of cohesive strength and moisture content in this study are very close to those in the study conducted by Zhang et al (2017) [20], interestingly. Meanwhile, the effect of moisture content on the friction angle of the coal specimen was also studied (Figure 7b).…”
Section: Effect Of Moisture Content On the Strength Properties Of Coalsupporting
confidence: 91%
“…The effect of moisture content on the friction angle was much less pronounced than that on cohesion, interestingly. This finding agreed well with that of Zhang et al (2017) [20], as they concluded that the internal friction angle was almost independent of the moisture content. In conclusion, the moisture content of 22.58% was recommended as the optimum moisture content for further tasks (e.g., water injection time and field water injection).…”
Section: Effect Of Moisture Content On the Strength Properties Of Coalsupporting
confidence: 90%
See 1 more Smart Citation
“…However, within the other areas, the coal surface morphology shows high integrity and compactness. These indicate that the clay minerals promote the growth of internal fissures and the formation of flaky structures via interactions with water …”
Section: Discussionmentioning
confidence: 98%
“…As wetting‐drying cycles could induce mechanical property deterioration via the original defects in a rock, the effect of wetting‐drying on coal would be more complex because coal is a porous and low wettability material . In addition, there are usually various clay minerals inside coal mass, and so the water‐coal interaction does not merely involve soaking and water adsorption.…”
Section: Introductionmentioning
confidence: 99%